2006
DOI: 10.1093/scan/nsl002
|View full text |Cite
|
Sign up to set email alerts
|

Alternative mechanisms for regulating racial responses according to internalvsexternal cues

Abstract: Personal (internal) and normative (external) impetuses for regulating racially biased behaviour are well-documented, yet the extent to which internally and externally driven regulatory processes arise from the same mechanism is unknown. Whereas the regulation of race bias according to internal cues has been associated with conflict-monitoring processes and activation of the dorsal anterior cingulate cortex (dACC), we proposed that responses regulated according to external cues to respond without prejudice invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
72
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 61 publications
8
72
1
Order By: Relevance
“…However, PD estimates did not differ as a function of interviewer race. This finding is consistent with past work showing that during an interracial interaction, participants exert additional control in order to deliver non-prejudice responses (Amodio, Kubota, Harmon-Jones, & Devine, 2006;Richeson & Shelton, 2003). Nevertheless, it was possible that individual differences in the degree of control would be associated with self-reported anxiety or cortisol reactivity.…”
Section: Weapons Identification Tasksupporting
confidence: 91%
“…However, PD estimates did not differ as a function of interviewer race. This finding is consistent with past work showing that during an interracial interaction, participants exert additional control in order to deliver non-prejudice responses (Amodio, Kubota, Harmon-Jones, & Devine, 2006;Richeson & Shelton, 2003). Nevertheless, it was possible that individual differences in the degree of control would be associated with self-reported anxiety or cortisol reactivity.…”
Section: Weapons Identification Tasksupporting
confidence: 91%
“…Interestingly, high-and low-prejudice participants differed only in their behavior, such that stronger PFC activity and P2 effects facilitated behavioral control only for low-prejudice participants. This finding is consistent with the idea that controlled processing may arise from different underlying motivations and may apply to different psychological and behavioral targets (Amodio et al, 2003(Amodio et al, , 2006.…”
Section: Pfc Activity and The Control Of Prejudicesupporting
confidence: 90%
“…However, they were assured their responses would be private and completely confidential. Past research has shown that this procedure is effective in engaging participantsʼ personal motivations to respond without prejudice while mitigating any normative concerns about appearing racist to others (Amodio et al, 2008;Amodio, Kubota, Harmon-Jones, & Devine, 2006). Hence, this procedure allowed us to examine the effect of personal attitudes on self-regulatory processes in the absence of normative concerns.…”
Section: Methodsmentioning
confidence: 99%
“…ACC activity was selectively greater on trials requiring stereotype inhibition, and the degree of subjects' ACC activity on these trials predicted their success at controlling the expression of stereotypes in task behaviour 123 . This finding has been replicated and extended in several studies using different tasks and with alternative ERP indices of ACC activity (for example, the error-related negativity and response-locked N2) [124][125][126][127] . These studies revealed, for example, that ACC activation in response to stereotype conflict occurs implicitly and without deliberation, is observed on a range of cognitive control tasks that require the inhibition of stereotype-based responses and is associated with an individual's motivation to respond without prejudice.…”
Section: Regulation Of Prejudice and Stereotypingsupporting
confidence: 56%